Clinical trial landscape for guided bone regeneration: trend analysis and future perspectives - Gui, Yuqing; Shen, Xinyue; Li, Hongying; Lou, Junyi; Cao, Junjie; Yu, Jiang; Luo, Zining; Geng, Tianxiang; Xie, Jiebin (Frontiers in Dental Medicine, 2025)
AimThis study aims to comprehensively analyse the developmental progress of bone graft materials and barrier membranes in the field of oral-maxillofacial bone regeneration, with a particular emphasis on emerging therapeutic approaches for bone regeneration.Materials and methodsThis study systematically searched 16 clinical trial registries using key terms such as “bone regeneration” and “osteoconduction” to identify relevant trials. The retrieved studies were then categorized and analysed on the basis of registration year, research phase, material/drug classification, and geographical distribution.ResultsIn the field of bone graft materials and barrier membranes, clinical trials involving synthetic bone graft materials (N = 90) and xenogeneic bone graft materials (N = 67) have been the most common. In the category of barrier membranes, collagen membranes still dominate (N = 53), whereas other natural membranes, such as amniotic and chorionic membranes, are in clinical trials. Resorbable polyester membranes (N = 24), titanium mesh (N = 13) and nonresorbable polytetrafluoroethylene membranes (N = 11) are commonly studied barrier membranes. Platelet-rich fibrin (PRF) (N = 71) is the most frequently used type of bioactive adjuvant. Some trials have explored the synergistic effects of statins (N = 17) and plant-derived active extracts (N = 16).ConclusionResearch on bone regeneration is undergoing a paradigm shift from the conventional “bone graft + barrier membrane” approach to integrated multicomponent strategies. These advanced strategies combine tunable biodegradable scaffolds, growth factors, and small-molecule drugs to achieve personalized and cost-effective bone defect repair. Future research priorities will focus on optimizing material degradation kinetics and spatial maintenance properties to enhance clinical outcomes.